Modifikasi Alat Monitoring Suhu dan Kelembaban Udara dengan IoT (Internet of Things) di Wilayah Terminal Bandara - Arnas, Yenni; Mediaswati, Cristina Novi; Savitri, Anak Agung Putu Cecilia; Putri, Kartika; Simanjuntak, Febrian; Paramartha, I Ketut Aditya (Jurnal Teknik Mekanikal Bandar Udara, 2023)
To efficiency time and energy in measuring temperature and humidity in all areas of the terminal area, the authors try to design a tool that functions to measure and record the results of temperature and humidity measurement data at each location in the area of the terminal area. The design of this tool can be an option or choice to consider because so far measurements have been carried out manually (visiting each location directly with a total of 25 locations with a distance of ± 120 meters per location). In addition, these measurements are also carried out 7 times a day for a period of measurement time one time, which is every 2 hours. With these factors, the authors try to modify the manual system to become a completely automatic system by utilizing the Blynk application as an application that will accommodate and be able to display the results of temperature and humidity measurements as well as the NodeMCU ESP8266 and DHT11 sensor as a medium for measuring temperature and humidity. With the implementation of the Internet of Things, Bylnk as the application of the Internet of Things, it is hoped that air temperature and humidity measurements at terminals can be more effective and targeted to take action if problems occur and to prevent problems from beginning. The purpose Bylink application will certainly help a lot in measuring temperature and humidity.